The status of women and of maternal and perinatal health in Turkey - Kültürsay, Nilgün (The Turkish Journal of Pediatrics, 2011)
Turkey has improved the status of women and the maternal and perinatal health statistics in the last decades. However, discrepancies between urban-rural and east-other regions continue, with some improvements. The education of girls is promoted and maternal age at marriage and at first delivery has increased. Birth control measures are increasingly used. Fertility rates decreased to 2.16 children per fertile woman. Antenatal care standards have improved, and achievement of deliveries by health care personnel and postnatal mother/newborn care has increased to 90%. The maternal death rate decreased to 19.5 in 100,000 pregnants. However, uneducated women marry earlier and have a higher risk of dying from pregnancy-related causes. Perinatal mortality decreased to 19 in 1,000 deliveries. Neonatal mortality rate decreased to 13 in 1,000 live deliveries. Uneducated mothers living in rural areas and having more children receive less antenatal and postnatal care and are more likely to lose their newborn. The major causes of neonatal deaths are prematurity and congenital abnormalities.